Overview of Medication Adherence in Pulmonary Tuberculosis Patients at the Pekauman Health Center, Banjarmasin City - Emellia, Emellia; Irawan, Angga; Syahlani, Ahmad (Universitas Ibn Khaldun Bogor, 2025)
Pulmonary tuberculosis is an infectious disease that can be life-threatening. Antituberculosis treatment aims to achieve patient recovery, with the success of therapy depending on patient adherence. This study aims to describe the adherence of pulmonary tuberculosis patients at the Puskesmas Pekauman Kota Banjarmasin. The study uses a descriptive survey method with a cross-sectional approach. The sample consists of 36 pulmonary tuberculosis patients selected through total sampling. The instrument used in this study is a questionnaire. The study shows that the majority of respondents are male (55.6%), late adulthood (27.8%), high school graduates (36.1%), private employees (44.4%), earning below the minimum wage (58.3%), with no family history (77.8%), and suffering from TB for more than 2 months (52.8%). Adherence among the majority of respondents, 35 out of 36 (97.2%), is high. A reminder system to support treatment adherence in pulmonary tuberculosis patients is highly necessary.